Об обнаружении пустот на границе контакта двухслойных систем - Сергиенко, В.Н.; Курочка, А.А.; Соколовский, В.И. (Геотехническая механика, 2009)
Описано двошарову фізичну модель, що включає геосередовище та бетонну оболонку.
Представлено результати експерименту по виявленню порожнин на межі шарів з використанням ємнісного датчика. The duplex physical model including Geological environment and a concrete casing is described. The results of experiment on revealing interstices on border of layers with use of the capacitive sensor are represented.